Size and genotype affect resistance to mortality caused by OsHV-1 in Crassostrea gigas - Degremont, Lionel (Aquaculture, 2013)
As with summer mortalities reported in France between 2001 and 2006, mortality caused by the Ostreid herpesvirus 1 (OsHV-1) in Crassostrea gigas affects mostly juveniles, although adults can also be impacted to a small extent. This could suggest that both mortalities have similar causes and that establishment of resistance, in particular to the Ostreid herpesvirus 1 (OsHV-1), depends on either the size or the age of oysters. The present study reports an investigation of both size and age using three cohorts produced during winter and three produced during summer. Each cohort contained oysters genetically selected to be resistant or susceptible to the summer mortality phenomenon, as well as unselected control oysters. Any abnormal mortality was recorded between production and placement in the field. Transfer to field conditions was then made over thirty deployments between July 2009 and September 2011. All mortalities occurred when seawater temperature was above 16 °C, which was termed the ‘risk’ period. For all deployments made during the risk period, mortality was observed within two weeks post-deployment and most episodes lasted over a week. For deployments made outside of the risk period,mortality occurred as soon as the next risk period began. The absence of detection of OsHV-1 at deployment, the presence of a high viral load of OsHV-1 (>10+6 DNA copies per mg of fresh tissue) on moribund oysters sampled during peak mortality, and the mortality kinetic all suggest that the mortalities can be attributed to this pathogen alone. The major finding of this study was that the resistance to mortality caused by OsHV-1 increased with both age and size, suggesting a maturation of the immune system against the virus. In field conditions, the relationship between mortality and size was stronger than the relationship between mortality and age. Regression equations of oyster size or age at the onset of the mortality event were derived to estimate the mortality due to OsHV-1. Although larger animals always tended to be ...